Eddy current examination of carbon fibres in carbon-epoxy composites and Kevlar. (14th November 2006) - Grimberg, R.; Savin, A.; Steigmann, R.; Bruma, A.
This paper proposes a method for eddy current non-destructive examination of carbon fibres from carbon epoxy composites as well as the regions impacted with bullets from Kevlar textures. In this aim, an eddy current focused micro sensor, send-receiver type with orthogonal coils was developed. The obtained data were post processed using an incoherent holographic technique. By a small modification of lift-off, the successive layers of fibres can be visualised and, implicitly, their integrity. Using a similar method, the boundaries of the region impacted by a bullet from Kevlar textures were completely emphasised.